Dynamika biologiczna polskich społeczności wiejskich z różnych systemów ekologicznokulturowych w XVIII i XIX wieku - Puch, Elżbieta Alicja (Polskie Towarzystwo Antropologiczne, 1993)
BIOLOGICAL DYNAMICS OF POLISH RURAL COMMUNITES FROM VARIOUS ECO-CULTURAL SYSTEMS IN THE 18TH AND 19TH CENTURIES. The problems was investigated taking into consideration births, deaths and marriages recorded in the parish registers of: Płużnica (Silesia), Pobiedr (Galicia) and Szczepanowo (Wielkopolska Region). Fluctuations in mortality and fertility, as well as changes in seasonality of births, deaths and entering into marriages were estimated. Mating, marital migration, opportunity of natural selection and the possibility of changes within gene pools were analyzed. The investigations have shown that the biological dynamics of the populations differed distinctly according to time, region and sociocultural factors.
BIOLOGICAL DYNAMICS OF POLISH RURAL COMMUNITES FROM VARIOUS ECO-CULTURAL SYSTEMS IN THE 18TH AND 19TH CENTURIES.